Transforming Public Policy Through a Gender Lens: an Impact Analysis on Women's Empowerment - Umasugi, Mohbir (LPPM Universitas PGRI Sumatera Barat, 2025)
Gender equality is a key national and global development goal, and is incorporated into various public policies in Indonesia. Various regulations have been implemented to support women's empowerment in the economic, political, and social sectors. However, the implementation of gender-based policies still faces various challenges, including structural constraints, patriarchal culture, and a lack of gender understanding in policy formulation. This study analyzes the impact of regulations on women's empowerment and the challenges faced in implementing gender-responsive policies. The analysis shows that despite affirmative action policies such as a 30% quota for women in parliament and employment protection, gaps in policy implementation persist. Social, cultural, and economic factors are key obstacles to achieving effective gender equality. Therefore, a more comprehensive strategy is needed, including policy reform, capacity building of state officials, and strengthening women's participation in decision-making. With a more inclusive approach, it is hoped that public policies in Indonesia can be more effective in promoting gender equality and women's empowerment in various sectors of life